Rare variant of MAP2K7 is associated with increased risk of COPD in southern and eastern Chinese. Issue 4 (24th January 2017) - Qiu, Fuman; Li, Yinyan; Lu, Xiaoxiao; Xie, Chenli; Nong, Qingqing; Wu, Di; Chen, Jiansong; Yang, Lei; Zhou, Yifeng; Lu, Jiachun
ABSTRACT: Background and objective: A wide range of common loci have been extensively screened and evaluated for their associations with various complex diseases; however, the relevance of rare variants causing missense substitutions in the protein‐coding genes in human diseases is still poorly understood. Methods: In this study, we conducted a two‐stage retrospective study of a total of 1791 patients with COPD and 1940 controls in southern and eastern Chinese to test relevancies of five rare variants (i.e. p.Glu116Lys, p.Asn118Ser, p.Arg138Cys, p.Ala195Thr and p.Leu259Phe) of human mitogen‐activated protein kinase kinase 7 ( MAP2K7 ) to COPD susceptibility. The effects of these loci on lung function were further estimated. Results: The p.Glu116Lys rare variant had significant associations with COPD risk. Compared to individuals with Glu/Glu wild‐genotype, those with 116Lys rare variants (Lys/Glu+Lys/Lys) had an increased risk of COPD (OR = 3.83, 95% CI: 2.64–5.56; P  = 1.45 × 10 −12 ). Meanwhile, the carriers with 116Lys rare variants (Lys/Glu+Lys/Lys) had lower pre‐forced expiratory volume in 1 s (pre‐FEV1 : 1.74 ± 0.70 vs 2.00 ± 0.68; P  = 3.97 × 10 −5 ) and lower pre‐FEV1 to pre‐forced vital capacity ratio (pre‐FEV1 /FVC: 0.68 ± 0.14 vs 0.75 ± 0.12; P  = 2.40 × 10 −10 ) than those with Glu/Glu genotype. However, for other rare variants, no significant association with either COPD risk or lung function was observed. Conclusion: Our data strongly suggest that the p.Glu116Lys rare variant in MAP2K7 predisposes its carriers to develop COPD, which would provide a useful genetic biomarker for COPD susceptibility in Chinese. Abstract : Based on a two‐stage retrospective study, we evaluated the association between rare variants in MAP2K7 and COPD risk. We found that the Glu116Lys rare variant exerted an elevated risk of COPD accompanied by worsening lung function and it might be a genetic biomarker for COPD susceptibility.